European Academy of Neurology guideline on the management of medication‐overuse headache. (19th May 2020) - Diener, H. C.; Antonaci, F.; Braschinsky, M.; Evers, S.; Jensen, R.; Lainez, M.; Kristoffersen, E. S.; Tassorelli, C.; Ryliskiene, K.; Petersen, J. A.
Abstract: Background: The frequent use of medication to treat migraine attacks can lead to an increase in migraine frequency and is called medication‐overuse headache (MOH). Methods: Based on the available literature in this guideline, the first step in patient management is education and counselling. Results: Patients with MOH should be managed by a multidisciplinary team of neurologists or pain specialists and behavioral psychologists. Patients in whom education is not effective should be withdrawn from overused drugs and should receive preventive treatment with drugs of proven efficacy. Patients with MOH in whom preventive treatment is not effective should undergo drug withdrawal. Drug intake can be abruptly terminated or restricted in patients overusing simple analgesics, ergots or triptan medication. In patients with long‐lasting abuse of opioids, barbiturates or tranquilizers, slow tapering of these drugs is recommended. Withdrawal can be performed on an outpatient basis or in a daycare or inpatient setting.